The Malaysian Social Contract: A Historical Perspective - Azfar, Mohd. Rusydi; Muslim, Nazri; Khalid, Kartini Aboo Talib @; Yaacob, Mashitoh (Journal of Ecohumanism, 2024)
This paper delves into the concept of social contract, a framework rooted in the diverse theories pioneered by Western philosophers, to expound on the unique facets of the Malaysian social contract. This concept elucidates different forms of agreement between the people and the ruler in establishing an organised society. Unique and central to Malaysia, this contract involves traditional elements integral to the Malay establishment, encompassing Islam, the Malay language, the special position of the natives and the institution of Malay rulers in addition to citizenship rights for qualified individuals. To comprehend the distinctiveness of the Malaysian social contract, it is imperative to explore its historical context, tracing back the compromise forged among the inter-ethnic groups towards the independence of the Federation of Malaya. This historical narrative reveals that the post-World War II is Malaysia’s state of nature. However, the Malaysian social contract extends beyond understanding and consensus of inter-ethnic groups namely the Malays and the non-Malays. It also incorporates the agreement between the populace as a whole and the sovereign Malay rulers. Enshrined in the Federal Constitution, traditional elements and balancing provisions ensure compliance with the mutually agreed-upon social contract for both the Malays and the non-Malays.